Attitudes of Bedouin and Jewish Physicians Towards the Medical Care for Persons with Intellectual Disability in the Bedouin Negev Community. A Pilot Study - Mohammed Morad; Tagrid Morad; Isack Kandel; Joav Merrick (The Scientific World Journal)
Change in the attitudes of staff or the public towards people with intellectual disability (ID) can impact their life and health, but that change has not been studied among physicians who belong to an ethnic minority undergoing dramatic social and economic transition. The goal of this study was to explore the change of attitudes of Negev Bedouin physicians serving their community and their satisfaction with policy, care, and knowledge in the field of ID. Seventeen community physicians (7 Bedouins and 10 Jewish) were interviewed using a simple questionnaire that consisted of items measuring attitude and satisfaction. The vast majority of the Bedouin and Jewish physicians had positive attitudes toward inclusion of those in the community with ID and were ready to provide the care needed in the community with special assistance. There was a need for further education in ID and more resources. There was a belief that there is discrimination between the Bedouin and Jewish community in the provision of care to people with ID. General dissatisfaction was expressed about the policy, resources, care provision, and expertise offered to Bedouins with ID. More efforts must be directed to empower the physicians with knowledge, expertise, and resources to handle the care of Bedouins with ID in a culturally appropriate way.